An Outbreak of Sodium Fluoroacetate (1080) Intoxication in Selenium- and Copper-Deficient Sheep in California - Giannitti, Federico (2013)
Sodium fluoroacetate is an organofluorine compound toxic to mammals, insects, and birds, currently registered for use only in livestock protection collars as a predacide in some North American states, with restricted use in California. A flock of 445 lambs and ewes in California were moved into a native pasture on a municipal refuse disposal site. Within 24 hours, 14 ewes were found dead, and the remaining sheep were moved off the site. Both ewes and lambs exhibited disoriented running, followed by apparent blindness, weakness, ataxia, coma, and death. Over the next 4 days, 63 ewes and 80 lambs died with a peak at 3 days after grazing the suspect pasture (157/445, 35% mortality). Two dead 4-month-old lambs and 2 ewes were submitted to the California Animal Health and Food Safety laboratory for necropsy. Grossly, there were bilateral diffuse pulmonary congestion and edema, hydrothorax and hydropericardium with fibrin clots, and multifocally extensive areas of epicardial petechiae, ecchymoses, and pallor. In 1 ewe, there was regional caudodorsal pulmonary hemorrhage and intraluminal tracheal clotted blood. Microscopically in all cases, there was multifocal acute myocardial degeneration and necrosis with nonsuppurative pleocellular myocarditis. Sodium fluoroacetate was detected in kidney from a lamb and a ewe at 27.5 and 12.5 parts per billion, respectively. All sheep were selenium deficient, and concurrent copper deficiency was diagnosed in 3. The pathological and toxicological findings were consistent with 1080 poisoning, possibly exacerbated by micronutrient deficiency. This outbreak raised an alert about the use of restricted products with potential lethal effect in animals in California.